Literature Review: The Effects of Covid-19 Pandemic-Driven Home Behavior in Housing Preference - Muhyi, Mahdaniar Maulidini; Adianto, Joko (Smart City, 2021)
This literature review is aimed to identify the possible correlation between Covid-19 pandemic and housing preferences. It is known that the pandemic has impacts on human activities and this also has an indirect effect on housing selection. We used a qualitative method by reviewing 52 papers and articles related to pandemic and residential real estate from March 2020 to May 2021. The review indicates that Covid-19 pandemic has induced to the housing preferences: fear of meeting people, fear of economic recession, and ‘stay at home’ lifestyle. The pandemic increases people’s needs to control their living space, including personal safety space, house expense, and the use of home space. This review will benefit real estate developers in Indonesia as reference of lifestyle regarding healthy residential building especially in the post-pandemic future.